2014
DOI: 10.1002/pmic.201400144
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis inGiardia duodenalisyields insights into strain virulence and antigenic variation

Abstract: Giardia duodenalis is a protozoan parasite of the small intestine in vertebrates, including humans. Assemblage A of G. duodenalis is one of the two discrete subtypes that infects humans, and is considered a zoonotic assemblage. Two G. duodenalis Assemblage A strains BRIS/95/HEPU/2041 and BRIS/83/HEPU/106, constituting virulent and control strains respectively, were analyzed in one of the first comparative shotgun proteomic studies performed in this parasite. Protein extracts were prepared using a multiplatform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 75 publications
3
32
0
Order By: Relevance
“…In total, there were 2 large functional clusters that varied between strains and life cycle stages; 'VSP/Furin-like/EGFlike' and 'ankyrin-repeat'. Both these clusters feature proteins from the Giardia variable genome already implicated in inter-and intra-assemblage variation [23,49,51]. These data reinforce the hypothesis that the diversity seen in such families at the genome level translates to crucial differences at the level of the expressed proteome between strains at both life cycle stages.…”
Section: Strain-specific Adaptations During Encystationsupporting
confidence: 66%
See 4 more Smart Citations
“…In total, there were 2 large functional clusters that varied between strains and life cycle stages; 'VSP/Furin-like/EGFlike' and 'ankyrin-repeat'. Both these clusters feature proteins from the Giardia variable genome already implicated in inter-and intra-assemblage variation [23,49,51]. These data reinforce the hypothesis that the diversity seen in such families at the genome level translates to crucial differences at the level of the expressed proteome between strains at both life cycle stages.…”
Section: Strain-specific Adaptations During Encystationsupporting
confidence: 66%
“…In a previous study, we examined strain variation between H-106 and B-2041 trophozoites from axenic culture, and found that surface antigen proteins from the VSP family varied in both number and subpopulation distribution between strains [23]. In this study we show that other proteins that we previously identified as differentially expressed between H-106 and B-2041 trophozoites are also differentially expressed in the corresponding cysts.…”
Section: Strain-specific Adaptations During Encystationmentioning
confidence: 54%
See 3 more Smart Citations